Anti-inflammatory activity of hydrolysed glucomannan from porang (Amorphophallus muelleri Blume) through inhibition response of nitric oxide production in lipopolysaccharide (LPS)-activated RAW 264.7 macrophage cells - Mochamad Affandi; Zamnia Wahyuli; Sudarminto Setyo Yuwono; Simon Bambang Widjanarko (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Few studies have been conducted on porang (Amorphophallus muelleri Blume) glucomannan (PGM) as anti-inflammatory drugs. The study aimed to evaluate the relationship between the use of sulfuric acid concentration in the hydrolysis process and the anti-inflammatory effects of PGM hydrolysates (PGMH) using the nitric oxide (NO) inhibition approach. PGMH is prepared by hydrolysing PGM with sulfuric acid (0.25N, 0.5N, and 1.0N concentration). This experimental study analysed the production of nitric oxide (NO) formation related to inflammation. Lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophage cells were treated with PGM and PGMH (62.5, 125, 250, and 500 micrograms per millilitres). The cytotropic substance was measured by using the Griess reaction assay. The analysis showed that the PGM and PGMH possessed more potent NO inhibitory activity than the positive control. PGMH 1.0N treatment had the highest inhibitory potential of NO production with an IC50 value of 353.1 micrograms per milliliters. Increasing the concentration of a PGMH 1.0N was inversely proportional to the decrease in NO production. PGMH 1.0N 500 micrograms per milliliter treatment significantly suppressed the production of NO. PGM and PGMH as alternative therapies stimulate the immune system in vitro significantly. The current study might be used as a preliminary guide for choosing the best concentrations of PGMH and sulfuric acid in future studies that aim to reduce inflammation and modulate the immune system.